Merangkul Feminis Cegah Ketidakadilan pada Istri dalam Kehidupan Rumah Tangga - Tawarika M. Pandiangan (Pusat Riset dan Inovasi Nasional, 2024)
Women suffer injustice not only through discrimination in the public world, but also through the way work is organized and income distribution within the family itself. The cruelest discrimination against women occurs when they have a family. Qualitative research method with a natural paradigm that relies on phenomenology. The approaches used are gender, intrinsic and anthropological approaches. The results show that family life patterns limit women's opportunities in many ways, by assigning them to unpaid work with low prestige; by not giving them equal opportunities for outside employment and education; by being forced to do most or all of the housework and childcare even though they also get paid. What is most disturbing is the suffering of women due to the altruism of marriage itself.